1987
DOI: 10.1243/pime_proc_1987_201_022_02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression and Expansion on Instantaneous Heat Transfer in Reciprocating Internal Combustion Engines

Abstract: Znstantaneous heat j u x at the surface of a cylinder head in a motored diesel engine has been measured, at various speeds, using a fast-response surface thermocouple. Heat frux during compression was found to be much larger than heat flux during expansion, the maximum heat flux occurred about 8" bqore top dead centre and there was a signij-icant heat flux even when gas temperature and wall temperature were equal. During expansion, heatflowed from the surface to the gas even though the bulk gas temperature was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 9 publications
(3 reference statements)
5
48
0
Order By: Relevance
“…There are some doubts however about the correctness of this method. Lawton [11] and Nijeweme et al [12] have reported non-zero heat fluxes at the moment of equal wall and gas temperature.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…There are some doubts however about the correctness of this method. Lawton [11] and Nijeweme et al [12] have reported non-zero heat fluxes at the moment of equal wall and gas temperature.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…1 [1][2][3]). Attempts were made and have been reported in the literature [1,3,4] to include this phenomenon in the conventional Nu-Re model by adding a complex phasing part to the bulk gas temperature -heat transfer correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1) has been solved subject to the boundary and initial conditions using a Crank-Nicolson finite difference scheme with Gauss-Seidel iteration similar to that described by [Lawton (1987)]. The wall temperature ratio, f (t) = Tw/T∞ varies with time, principally because of the variation in T∞.…”
Section: Unsteady Heat Transfer Modellingmentioning
confidence: 99%
“…The upper estimate is for a turbulent case and uses a thermal conductivity value 25 times larger than the laminar value. Although this approach to modelling the turbulent transport is somewhat arbitrary, it was reasonably successful in the IC engine work of [Lawton (1987)] where peak heat flux values were correctly estimated to within about 10% (although discrepancies of 50% or more were typically apparent at other times during the IC engine cycle).…”
Section: Heat Fluxmentioning
confidence: 99%